Estimating Threshold Level of Carbon Tax on CO2 Emissions in South Africa Economy - Mbua, Mofema Victor; Mah, Gisele (International Journal of Energy Economics and Policy, 2025)
In recent decades, the growing importance of carbon taxes has led researchers to investigate their drivers and effects on economic growth and the environment. This study analyses the relationship between carbon emissions, carbon tax, and economic growth in South Africa, utilizing data from 1993 to 2022 and was collected from World Development Bank, International Energy Agency, and the South African Reserve Bank. Employing a threshold method, the study estimates the carbon tax necessary to reduce CO2 emissions while stimulating growth. The analysis indicates that carbon tax serves as a regime switch, with a bootstrap value of 0.019, which is below the 0.05 threshold. The findings reveal a positive relationship between carbon tax and carbon emissions, GDP and CO2 emission across both regimes. Consequently, it is suggested that South Africa should continue increasing its carbon tax, as it has not yet reached its maximum threshold for effectively reducing CO2 emissions.